EU sustainability criteria for biofuels: uncertainties in GHG emissions from cultivation. Issue 4 (July 2012) - Ahlgren, Serina; Röös, Elin; Di Lucia, Lorenzo; Sundberg, Cecilia; Hansson, Per-Anders
Background: Cultivation of raw material represents a large proportion of biofuels´ GHG emissions. The EU renewable energy directive 2009/28/EC specifies a GHG emission default value for cultivation of biofuel raw material (23 g CO2 -e/MJ ethanol for wheat). The aim of this study was to quantify the uncertainty in GHG emissions for wheat cultivation in Sweden, considering uncertainty and variability in data at farm level.Results: Two levels of data collection at farm level were analyzed; simple (only yield and amount of N) and advanced (also including amounts and types of energy). The 2.5–97.5 percentile uncertainty for Swedish winter wheat was 20–27 g CO2 -e/MJ, which can be considered large in the context of the Directive's threshold of 23 g (to two significant figures).Conclusion: It is concluded that quantifying GHG emissions in order to regulate biofuels is a difficult task, especially emissions from cultivation, since these are biological systems with large variability.